2003
DOI: 10.1038/ng1276
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in ARFGEF2 implicate vesicle trafficking in neural progenitor proliferation and migration in the human cerebral cortex

Abstract: Disruption of human neural precursor proliferation can give rise to a small brain (microcephaly), and failure of neurons to migrate properly can lead to an abnormal arrest of cerebral cortical neurons in proliferative zones near the lateral ventricles (periventricular heterotopia). Here we show that an autosomal recessive condition characterized by microcephaly and periventricular heterotopia 1 maps to chromosome 20 and is caused by mutations in the gene ADP-ribosylation factor guanine nucleotide-exchange fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
318
1
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 352 publications
(330 citation statements)
references
References 29 publications
7
318
1
4
Order By: Relevance
“…Regulation of cell fate by αSnap may affect other organs, but previous analysis has not shown hypoplasia of other organs 1 in hyh mice, perhaps because other tissues regulate size postnatally, whereas the postnatal brain contains largely postmitotic neurons. Other genes that affect the size of the central nervous system in humans commonly do not affect other organs, even when they are ubiquitously expressed 27,28 29 , analysis of the hyh mutant supports this role and provides an opportunity to examine the role of apical vesicle trafficking in other aspects of neural development. The hyh mutant has additional defects in cerebellar development, neuronal migration and axonal pathfinding (data not shown), suggesting roles for apical trafficking in these processes.…”
mentioning
confidence: 85%
“…Regulation of cell fate by αSnap may affect other organs, but previous analysis has not shown hypoplasia of other organs 1 in hyh mice, perhaps because other tissues regulate size postnatally, whereas the postnatal brain contains largely postmitotic neurons. Other genes that affect the size of the central nervous system in humans commonly do not affect other organs, even when they are ubiquitously expressed 27,28 29 , analysis of the hyh mutant supports this role and provides an opportunity to examine the role of apical vesicle trafficking in other aspects of neural development. The hyh mutant has additional defects in cerebellar development, neuronal migration and axonal pathfinding (data not shown), suggesting roles for apical trafficking in these processes.…”
mentioning
confidence: 85%
“…Wang et al (25) found that overexpression of GFP-Exo70 (but not GFP-Exo84) resulted in the disruption of microtubule architecture in the area of cytoplasm under regions of plasma membrane protrusions, and microtubule polymerization in vitro was inhibited by recombinant Exo70. The interaction of BIG2 with Exo70 in these processes suggests a mechanism for the congenital defects described in two families with mutations in the BIG2 gene (7).…”
Section: Discussionmentioning
confidence: 99%
“…They appear to colocalize at the trans-Golgi network (4,5), but move independently among intracellular compartments, e.g., after serum starvation of HepG2 cells, BIG1, but not BIG2, is present in nuclear structures (6). BIG2 mutations were related to an autosomal recessive periventricular heterotopia with microcephaly, a congenital human developmental disorder (7). No disease involving BIG1 has been reported.…”
mentioning
confidence: 99%
“…In yeast, Gea1p and Gea2p are functionally redundant in that one or the other can be deleted with no detectable effect on growth rate or rates of transport to the cell surface and vacuole, whereas a gea1⌬ gea2⌬ double mutant is inviable (Peyroche et al, 1996. A similar situation is likely true of the BIG1-BIG2 pair in mammalian cells, given their extensive sequence homology (74% identity; Togawa et al, 1999;Yamaji et al, 2000) and the fact that a human disease (autosomal recessive periventricular heterotopia) is caused by almost complete deletion of the BIG2 gene (Sheen et al, 2004). The fact that these affected individuals with no BIG2 function are born and live several years (albeit with severe abnormalities) indicates that at the cellular level, there is a high level of redundancy between BIG1 and BIG2 for essential functions.…”
Section: Introductionmentioning
confidence: 94%